Effect of supplementation with groundnut cake and phosphorus on utilisation of millet stover by sheep and excretion of nutrients - Sangare, M.; Fernández Rivera, S.; Hiernaux, Pierre H.Y.; Pandey, V.S. (Institut de Medecine Tropicale Prince, 2002)
An experiment was conducted during the dry season in 1998 to determine the influence of supplementation with groundnut cake (GC) (0, 2.5, 5 and 7.5 g kg-1 LW) and phosphorus (P) (0 and 3 g day-1 animal) on diet and millet stover intake and digestibility, sheep growth rate and nutrient excretion. Total digestible organic matter intake (DOMI, g kg-1 LW 0.75) increased 4.24 (+ or -) 1.26 g per g of GC and decreased -0.31 (+ or -) 0.16 g per g GC2, and tended to increase (P = 0.10) with P supplementation. Millet stover intake (g kg-1 LW) was related to GC level by both linear (+1.79 (+ or -) 0.53 g per g GC) and quadratic (-0.20 (+ or -) 0.07 g per g GC2) functions and to P supplementation by linear function (0.87 (+ or -) 0.46 g per g P). No effect of GC X P interaction was observed. At equal level of GC, P supplementation increased stover intake by 2 to 20 %. Diet digestibility increased linearly (P < 0.01) with GC level, but no effect of P supplementation was observed. Digestibility of NDF was unaffected by either GC or P level. Animals supplemented with P had adequate P (0.24 %) in their diet in contrast with those unsupplemented (0.05 to 0.18 %). Live weight gain (g day-1) increased 22.10 (+ or -) 3.10 g per g GC and decreased -1.52 (+ or -) 0.39 g GC2. Live weight gain response to P supplementation (7.33 (+ or -) 1.66 g per of P) was independent of GC level. Nitrogen concentration in faeces (g kg-1 FDM) increased linearly both by GC and P supplementation, whereas urinary N (g l-1) was only influenced by GC level. Faecal P (g kg-1 FDM) increased about three-fold with P supplementation. It is concluded that an adequate capture of the additional N and P voided following supplementation could enhance the sustainability of mixed farming systems in the Sahel.